2008
DOI: 10.1088/1751-8113/41/31/312004
|View full text |Cite
|
Sign up to set email alerts
|

A note on the quantum-tail effect on fusion reaction rate

Abstract: A study is made of the power-law tail effect in the quantum particle distribution over momentum on the nuclear fusion reactions. Our results do not support the idea of averaging the fusion reaction cross-section over the momentum distribution, postulated and used in many publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The accuracy of this approach is discussed further below where the results of calculations are shown for the full formula (2), simplified equation (17), and approximate analytical estimations (57) and (70). This eliminates the issues raised in the paper [16] on the validity of such a method.…”
Section: Analytical Estimates For Reaction Rates For Model Dis-tribut...mentioning
confidence: 95%
See 1 more Smart Citation
“…The accuracy of this approach is discussed further below where the results of calculations are shown for the full formula (2), simplified equation (17), and approximate analytical estimations (57) and (70). This eliminates the issues raised in the paper [16] on the validity of such a method.…”
Section: Analytical Estimates For Reaction Rates For Model Dis-tribut...mentioning
confidence: 95%
“…In the literature [16,17] there was some criticism, connected with the use of the asymptotical presentation of a single-particle distribution function for calculation of reaction rates, including fusion rates. The problem is that in reality we must use the product of distribution functions over momentum in the laboratory frame for both reacting particles and due to power low tails, not Maxwellian ones, it is hard to perform analytical integration of the reaction cross-section, depending on particles relative momentum in their center of mass.…”
Section: Introductionmentioning
confidence: 99%
“…For nonrelativistic Coulomb particles, γ(p) ∝ E −3/2 p , therefore the tail decays as w qt ∝ E −7/2 p . 1 This approach was criticized by Bahcall et al [5] and by Zubarev [41]. Bahcall for the reaction rate represents the density of states and should not be confused with the expectation values of particle momenta, distributed according to w mod (E p ).…”
Section: "Quantum Tail" In Energy Distributionmentioning
confidence: 99%
“…Zubarev [41] put forward another argument. He noted that the pp-fusion rates calculated with w B (E) and with w mod (E) differ by three orders of magnitude for the Sun, and concluded that in the second case "one has neglected the coupling between the various probability amplitudes of velocity which is introduced by the quantum uncertainty."…”
Section: "Quantum Tail" In Energy Distributionmentioning
confidence: 99%